Nanoparticles and cancer therapy: Perspectives for application of nanoparticles in the treatment of cancers - Aghebati‐Maleki, Ali; Dolati, Sanam; Ahmadi, Majid; Baghbanzhadeh, Amir; Asadi, Milad; Fotouhi, Ali; Yousefi, Mehdi; Aghebati‐Maleki, Leili (Journal of cellular physiology, 2020)
Rapid growth in nanotechnology toward the development of nanomedicine agents holds massive promise to improve therapeutic approaches against cancer. Nanomedicine products represent an opportunity to achieve sophisticated targeting strategies and multifunctionality. Nowadays, nanoparticles (NPs) have multiple applications in different branches of science. In recent years, NPs have repetitively been reported to play a significant role in modern medicine. They have been analyzed for different clinical applications, such as drug carriers, gene delivery to tumors, and contrast agents in imaging. A wide range of nanomaterials based on organic, inorganic, lipid, or glycan compounds, as well as on synthetic polymers has been utilized for the development and improvement of new cancer therapeutics. In this study, we discuss the role of NPs in treating cancer among different drug delivery methods for cancer therapy. In recent years, nanoparticles (NPs) have repetitively been reported to play a significant role in modern medicine. They have been analyzed for different clinical applications, such as drug carriers, gene delivery to tumors, and contrast agents in imaging.In this review, we discuss the role of NPs in treating cancer among different drug delivery methods for cancer therapy.